Pengaruh PPh Badan, CR, Tato Terhadap ROA Sektor F&B yang Terdaftar di BEI Periode 2022-2025 - Sheva Widyawan, Christian; Hadi Saputra, Dian Festiana; Setyowati, Lilis; Purwantoro, Purwantoro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to examine the effect of Corporate Income Tax, Current Ratio, and Company Performance on Return On Assets in Food and Beverage sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. This research employs an associative quantitative approach using secondary data from annual financial statements. The sample was selected using a purposive sampling method, resulting in 29 companies with a total of 116 panel data observations over four years. The independent variables used are Corporate Income Tax proxied by the tax to book ratio (TBR), Current Ratio (CR), and Company Performance proxied by Total Asset Turnover (TATO), while the dependent variable is Return On Assets (ROA). Data analysis was conducted using multiple linear regression with IBM SPSS 25 software. The results show that partially, Corporate Income Tax, Current Ratio, and Company Performance have no significant effect on Return On Assets. Simultaneously, the three variables also have no significant effect on Return On Assets, with a coefficient of determination (R²) of 0.024, indicating that the variation in ROA is largely explained by factors outside this research model.